Inflammation-mediated fibroblast activation and immune dysregulation in collagen VII-deficient skin - Anderson-Crannage, Morgan; Ascensión, Alex M.; Ibanez-Solé, Olga; Zhu, Hongwen; Schaefer, Edo; Ottomanelli, Darcy; Hochberg, Bruno; Pan, Jian; Luo, Wen; Tian, Meijuan; Chu, Yaya; Cairo, Mitchell S.; et al. (Frontiers in Immunology, 2023)
Inflammation is known to play a critical role in all stages of tumorigenesis; however, less is known on how it predisposes the tissue microenvironment preceding tumor formation. Recessive dystrophic epidermolysis bullosa (RDEB), a skin-blistering disease secondary to COL7A1 mutations and associated with chronic wounding, inflammation, fibrosis, and cutaneous squamous cell carcinoma (cSCC), models this dynamic. Here, we used single-cell RNA sequencing (scRNAseq) to analyze gene expression patterns of skin cells from a mouse model of RDEB. We uncovered a complex landscape within the RDEB dermal microenvironment that exhibited altered metabolism, enhanced angiogenesis, hyperproliferative keratinocytes, infiltration and activation of immune cell populations, and inflammatory fibroblast priming. We demonstrated the presence of activated neutrophil and Langerhans cell subpopulations and elevated expression of PD-1 and PD-L1 in T cells and antigen presenting cells, respectively.Unsupervised clustering within the fibroblast population further revealed two differentiation pathways in RDEB fibroblasts, one toward myofibroblasts and the other towards a phenotype that shares the characteristics of inflammatory fibroblast subsets in other inflammatory diseases as well as the IL1-induced inflammatory cancer-associated fibroblasts (iCAFs) reported in various cancer types. Quantitation of inflammatory cytokines indicated dynamic waves of IL-1α, TGFβ1, TNF, IL-6, and IFNγ concentrations, along with dermal NFκB activation preceding JAK/STAT signaling. We further demonstrated divergent and overlapping roles of these cytokines in inducing inflammatory phenotypes in RDEB patient-as well as RDEB mousederived fibroblasts together with their healthy controls. In summary, our data has suggested a potential role of inflammation, driven by chronic release of inflammatory cytokines such as IL-1, in creating an immune suppressed dermal microenvironment that underlies RDEB disease progression.